Cost-effectiveness of apixaban vs. current standard of care for stroke prevention in patients with atrial fibrillation - Dorian, Paul (Oxford University Press, 2014)
AIMS: Warfarin, a vitamin K antagonist (VKA), has been the standard of care for stroke prevention in patients with atrial fibrillation (AF). Aspirin is recommended for low-risk patients and those unsuitable for warfarin. Apixaban is an oral anticoagulant that has demonstrated better efficacy than warfarin and aspirin in the ARISTOTLE and AVERROES studies, respectively, and causes less bleeding than warfarin. We evaluated the potential cost-effectiveness of apixaban against warfarin and aspirin from the perspective of the UK payer perspective. RESULTS AND METHODS: A lifetime Markov model was developed to evaluate the pharmacoeconomic impact of apixaban compared with warfarin and aspirin in VKA suitable and VKA unsuitable patients, respectively. Clinical events considered in the model include ischaemic stroke, haemorrhagic stroke, intracranial haemorrhage, other major bleed, clinically relevant non-major bleed, myocardial infarction, cardiovascular hospitalization and treatment discontinuations; data from the ARISTOTLE and AVERROES trials and published mortality rates and event-related utility rates were used in the model. Apixaban was projected to increase life expectancy and quality-adjusted life years (QALYs) compared with warfarin and aspirin. These gains were expected to be achieved at a drug acquisition-related cost increase over lifetime. The estimated incremental cost-effectiveness ratio was £11 909 and £7196 per QALY gained with apixaban compared with warfarin and aspirin, respectively. Sensitivity analyses indicated that results were robust to a wide range of inputs. CONCLUSIONS: Based on randomized trial data, apixaban is a cost-effective alternative to warfarin and aspirin, in VKA suitable and VKA unsuitable patients with AF, respectively.